MARCH8 Suppresses Tumor Metastasis and Mediates Degradation of STAT3 and CD44 in Breast Cancer Cells - Chen, Wenjing; Patel, Dhwani; Jia, Yuzhi; Yu, Zihao; Liu, Xia; Shi, Hengliang; Liu, Huiping (Cancers, 2021)
Protein stability is largely regulated by post-translational modifications, such as ubiquitination, which is mediated by ubiquitin-activating enzyme E1, ubiquitin-conjugating enzyme E2, and ubiquitin ligase E3 with substrate specificity. Membrane-associated RING-CH (MARCH) proteins represent one novel family of transmembrane E3 ligases which target glycoproteins for lysosomal destruction. While most of the MARCH family members are known to degrade membrane proteins in immune cells, their tumor-intrinsic role is largely unknown. In this study, we found that the expression of one MARCH family member, MARCH8, is specifically downregulated in breast cancer tissues and positively correlated with breast cancer survival rate according to bioinformatic analysis of The Cancer Genomic Atlas (TCGA) dataset. MARCH8 protein expression was also lower in a variety of human breast cancer cell lines in comparison to immortalized human mammary epithelial MCF-12A cells. Restoration of MARCH8 expression induced apoptosis in human breast cancer cell lines MDA-MB-231 and BT549. Stable expression of MARCH8 inhibited tumorigenesis and lung metastases of MDA-MB-231 cells in mice. Moreover, we discovered that the breast cancer stem-cell marker and metastasis driver CD44, a membrane protein, interacts with MARCH8 and is one of the glycoprotein targets subject to MARCH8-dependent lysosomal degradation. Unexpectedly, we identified a nonmembrane protein, signal transducer and transcription activator 3 (STAT3), as another essential ubiquitination target of MARCH8, whose degradation through the proteasome pathway is responsible for the proapoptotic changes mediated by MARCH8. These findings highlight a novel tumor-suppressing function of MARCH8 in targeting both membrane and nonmembrane protein targets required for the survival and metastasis of breast cancer cells.